Homicides Disguised as Staged Suicides. Issue 2 (June 2020) - Prahlow, Samuel P.; Cohle, Stephen; Shattuck, Brandy; Prahlow, Joseph A.
Determining the correct cause and manner of death are among the chief responsibilities of the forensic pathologist. When confronted with a case having a questionable manner of death, it is important for scene evidence, witness statements, and forensic autopsy findings to be thoroughly reviewed before certifying the manner of death. Herein three gunshot wound cases are presented which initially were suspected to be suicides but were instead determined to be homicides through full investigations with correlation to autopsy findings.